The link between social media exposure and students’ moral reasoning and environmental concern: A generational analysis in Chile - Barrera Verdugo, Gustavo Alfonso. (Cogent OA, 2023)
Currently, social media is a fundamental source of information for higher education students, and universities are seeking to strengthen the ethical training and environmental concern of their students enrolled in engineering and business careers since they should lead teams and make relevant decisions in private or public organizations, affecting their subordinates, clients, suppliers and the environment. There is little information about the relationship between exposure to social media platforms and the level of moral reasoning and environmental concern of students enrolled in these areas, differentiating such relationships among younger students who are part of the centennial generation and older ones. To address this knowledge gap, this research analyses the responses of 237 Chilean engineering and business students to an online self-report survey through the Mann-U Wilcoxon test and Spearman correlation coefficients. Students were selected through convenience sampling during the 2020–2021 academic year. The results suggest that there is a positive relationship between the frequency of exposure to social media and the aforementioned concepts and that this relationship is more prominent in the centennial generation. Significant differences among the social media platforms are also supported. WhatsApp is a more transversal social media platform that shows significant correlations in both the younger and older students. This research highlights that social media platforms can be a relevant tool to strengthen the moral reasoning and environmental concern of engineering students who will lead people in organizations.
Keywords: Centennial generation; Environmental concern; Moral reasoning; Educación superior; Medio social